Influence of Bio-Stimulant to Rooting and Biomass of Sugarcane Setts at Pre-Tillering Stage - Oñal, Jr., Paulino A; Garcia, Jeff Gregorr A.; de la Cruz, Amie E.; Pitallar, Jewel V. (Future Science / FSH-PH Publications, 2024)
Sugarcane is an important crop in the Philippines planted throughout the country but is most abundant in the Visayas and particularly on Negros Island. This study aims to determine the effect of the application of different concentrations of bio-stimulant on enhancing root and biomass accumulations at the pre-tillering stage of the sugarcane plant. The study was conducted at the University of Negros Occidental – Recoletos School of Agriculture, Philippines last December 6, 2023, to February 6, 2024. One hundred pieces of two-eyed cane points of RC-88 were used as planting materials. Soaking the cane points in water was done for 24 hours. Thereafter they were removed from water and air-dried for 30 minutes. The bio-stimulant was prepared before the application based on the study protocol. The bio-stimulant was diluted in distilled water and applied at the base of the plant using a measuring cup for even distribution. Regular monitoring for the presence of pests/diseases was done including watering. There were five (5) treatments, replicated four (4) times using Complete Randomized Design (CRD). Statistical analysis revealed that most of the characteristics of sugarcane plants significantly correlated with roots and biomass accumulation when applied with different levels of concentrations of bio-stimulant concentration at the pre-tillering stage of sugarcane. The use of 500ml Bio-stimulant significantly influenced the germination, tiller height, weight of tillers, weight of roots, length of roots, and biomass. This study recommends the use of 500ml bio-stimulant in enhancing the rooting and biomass accumulation of sugarcane setts at pre-tillering stage.